Linkage of hereditary haemorrhagic telangiectasia to chromosome 9q34 and evidence for locus heterogeneity. - Heutink, P (1994)
Hereditary haemorrhagic telangiectasia (HHT) is an autosomal dominant disorder with unknown pathophysiology that is characterised by arteriovenous lesions and recurrent haemorrhage in virtually every organ. Linkage of HHT to markers on chromosome 9q has recently been reported. In this study we report confirmation of this localisation in three unrelated families of Dutch origin. A fourth unrelated HHT family, in which considerably fewer pulmonary arteriovenous malformations (PAVM) were present, yielded evidence for non-linkage to this region. We conclude that HHT is a genetically heterogeneous disorder and our results indicate that the presence of PAVM may be more common in patients with a chromosome 9 linked form of HHT than in patients with the non-linked form.